Antioxidant potential of Indian medicinal plant in Phyllanthus amarus L. under supplementary UV-B radiation - K.C. Ravindran, A. Indrajith (Recent Research in Science and Technology, 2009)
The stratospheric ozone depletion and enhanced solar ultraviolet-B (UV-B) irradiance may have adverse impact on living organism. The impact of UV-B radiation (UV-B, 280 320nm) on growth, biochemical and antioxidant enzymes activity was studied in Phyllanthus amarus (L.) seedling, commonly used as a green manure. The supplementary UV-B radiation significantly decreased the growth, development and changes in UV-B absorbing compounds such as anthocyanin and flavonoids. The antioxidant enzymes were unaffected and showed an enhanced activities in peroxidase, superoxide dismutase, Polyphenoloxidase and phenylalanine ammonia- lyase except catalase in UV-B irradiated seedling. Phyllanthus amarus seedling tries to counteract high level of reactive oxygen species produce under UV-B stress through the increased activities of antioxidant enzyme. We suggest that Phyllanthus amarus is resistant against UV-B radiation damage and the possible negative effect of additional UV-B radiation on the growth of seedling may have been effectively balanced by the UV-B radiation stress through increase in UV absorbing compound and antioxidant enzymes.